Rancang Bangun Alat Pendeteksi Kesegaran Ikan Berbasis Internet Of Things (IoT) - Risky Pratama (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Design and Development of an Internet of Things (IoT)-Based Fish Freshness Detection Device. Guided by Mrs. Henna Nurdiansari, S.T., M.T., M.Sc. and Mrs. Monika Retno Gunarti, S.Si.T., M.Pd. Indonesia has a great potential in fish production, reaching 12 million tons annually, accompanied by an increase in fish consumption. However, significant challenges arise regarding food safety, especially concerning the sale of non-fresh fish and the presence of formalin. As an innovative solution, a fish freshness and formalin detector based on IoT was developed. This device utilizes the TCS3200 sensor to detect color intensity and the HCHO sensor to detect formalin. This research employed the Research and Development (R&D) method to produce an effective detection device. When the LED is green without a buzzer sound and the LCD displays